Fujairah’s Castles and Forts as Cornerstones of Urban and Demographic Development: A Study in the History of Fujairah’s Forts and Their Impact on the Geographical Environment: القلاع والحصون بمنطقة الفجيرة بوصفها مرتكزات للتطور الحضري والسكاني :دراسة في تاريخ قلاع الفجيرة وتأثيرها على محيطها الجغرافي - Amnah Ahmed Saber Mohamed Aldhanhani; Abdul Hamid , Faisal @ Ahmad Faisal; Shu’aibu Umar Gokaru (Journal Al-Muqaddimah, 2026)
This research represents an exploratory attempt employing a historical methodology. It provides a comprehensive analysis of the pivotal role played by castles and forts in the Emirate of Fujairah, where they served as fundamental factors in shaping settlement patterns and influenced the region’s urban and demographic development. Moving beyond their original purpose as defensive installations, the study argues that these forts functioned as integrated environmental catalysts that fostered the sedentarization of nomadic communities. They played a primary role in securing vital resources that incentivized human settlement—such as water and agricultural land—and in protecting strategic trade routes. Through investigative case studies of major forts like Fujairah Fort and Al Bithnah Fort, the research explores the symbiotic relationship between a fort and its surrounding settlement. It also addresses the functional transformation of these castles in the modern era, from symbols of tribal authority to icons of national identity and economic resources through cultural tourism. The research concludes that Fujairah’s forts were not merely silent witnesses to history but were active drivers in shaping the demographic and economic map of the eastern coast of the United Arab Emirates.